2019
DOI: 10.3233/jad-180879
|View full text |Cite
|
Sign up to set email alerts
|

Novel Blood Biomarkers that Correlate with Cognitive Performance and Hippocampal Volumetry: Potential for Early Diagnosis of Alzheimer’s Disease

Abstract: Background: Differential diagnosis of people presenting with mild cognitive impairment (MCI) that will progress to Alzheimer's disease (AD) remains clinically challenging. Current criteria used to define AD include a series of neuropsychological assessments together with relevant imaging analysis such as magnetic resonance imaging (MRI). The clinical sensitivity and specificity of these assessments would be improved by the concommitant use of novel serum biomarkers. The branched chain aminotransferase proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
(45 reference statements)
2
13
0
Order By: Relevance
“…However, further studies are required to fully determine the impact of increased BCAT levels in AD brain. More recently, we reported that serum BCAT was also higher in AD individuals relative to healthy agematched controls (Hudd et al 2019). In this study we adopted a combined approach to generate a differential diagnosis of people presenting with MCI that will progress to AD.…”
Section: Glutamate Excitotoxicitymentioning
confidence: 99%
“…However, further studies are required to fully determine the impact of increased BCAT levels in AD brain. More recently, we reported that serum BCAT was also higher in AD individuals relative to healthy agematched controls (Hudd et al 2019). In this study we adopted a combined approach to generate a differential diagnosis of people presenting with MCI that will progress to AD.…”
Section: Glutamate Excitotoxicitymentioning
confidence: 99%
“…A recent research study has documented that blood BCAT proteins were increased in patients with AD in comparison to healthy controls [8]. Blood BCAT proteins and glutamate increase the sensitivity and specificity of Montreal Cognitive Assessment in correctly discriminating healthy subjects and subjects with AD, which is useful for an early diagnosis of AD [8].…”
Section: Aa Alterations Linked To Nutritional Statementioning
confidence: 99%
“…A recent research study has documented that blood BCAT proteins were increased in patients with AD in comparison to healthy controls [8]. Blood BCAT proteins and glutamate increase the sensitivity and specificity of Montreal Cognitive Assessment in correctly discriminating healthy subjects and subjects with AD, which is useful for an early diagnosis of AD [8]. The increase in blood BCAT paralleled the increased levels of BCATs found previously in the hippocampus, frontal and temporal cortex, in a post-mortem analysis of AD patients [64].…”
Section: Aa Alterations Linked To Nutritional Statementioning
confidence: 99%
See 1 more Smart Citation
“…Branched chain amino acids (BCAAs), including leucine, isoleucine, and valine, are essential amino acids necessary for protein synthesis, but when found in excess, impact energy homeostasis [13][14][15]. Recent work demonstrated that elevated dietary BCAA intake is associated with obesity and insulin resistance in both humans and rodents [16,17], and plasma BCAA levels are highly predictive of T2D development in normoglycemic individuals [18].…”
Section: Introductionmentioning
confidence: 99%